Features of manifestation and neutralization of risks of economic security in the processes of digitalization - V. M. Yakovlev (Путеводитель предпринимателя)
The article deals with topical issues of the digital economy (CE) formation taking into account the theoretical substantiation of the need for such transformations in the processes of digitalization, as a result of which data in digital form become a key factor of production in all spheres of socio-economic activity. The essence is Determined by the content and (CE), the nature of the manifestations in various sectors of economic activity, taking into account the emergence of digital risk, increasing the negative consequences and threats to the economic security of enterprises and the economy. In this case we specify the tools and mechanisms of the transformative impact of the digitization of processes, among which are the blockchain technology, of Neurotechnology, artificial intelligence, robotics. The characteristic of predicted risks of digitalization is given, and also the planned effects on the basis of which, on the one hand, conditions of elimination of routine processes, increase of labor productivity, taking into account elimination of elements of shadow economy, fraud and corruption, on the other hand, options of strengthening of the same negative forms of activity, taking into account options of their strengthening in interaction with new digital risks are revealed. On the basis of the work done, proposals are made to improve the control of emerging standard risks, taking into account the identification and prevention and elimination of new digital risks.